Unisexual flower initiation in the monoecious Quercus suber L.: a molecular approach - Sobral, Rómulo Sacramento (2020)
Several plant species display a temporal separation of the male and female flower organ development to enhance outbreeding; however, little is known regarding the genetic mechanisms controlling this temporal separation. Quercus suber is a monoecious oak tree with accentuated protandry: in late winter, unisexual male flowers emerge adjacent to the swollen buds, whereas unisexual female flowers emerge in the axils of newly formed leaves formed during spring (4-8 weeks after male flowering). Here, a phylogenetic profiling has led to the identification of cork oak homologs of key floral regulatory genes. The role of these cork oak homologs during flower development was identified with functional studies in Arabidopsis thaliana. The expression profile throughout the year of flower regulators (inducers and repressors), in leaves and buds, suggests that the development of male and female flowers may be preceded by separated induction events. Female flowers are most likely induced during the vegetative flush occurring in spring, whereas male flowers may be induced in early summer. Male flowers stay enclosed within the pre-dormant buds, but complete their development before the vegetative flush of the following year, displaying a long period of anthesis that spans the dormant period. Our results portray a genetic mechanism that may explain similar reproductive habits in other monoecious tree species.